La caducidad en los procedimientos de determinación de responsabilidades: estudio de casos. - Silva Banderas, Juan Andrés (2022)
The Comptroller General of the State is the body called to carry out the control of State institutions, in terms of the fulfillment of its objectives and the proper use of public resources. According to article 2 of the Organic Law of the General Comptroller of the State (LOCGE), this entity is invested with the competence to determine administrative and/or civil responsibilities against public servants and persons from the private sector. However, to make effective the administrative act that declares the existence of any of these responsibilities, it must undergo a procedure. This article aims to analyze the legal consequences that the inactivity of the control action produces in the procedure and the effects it generates. In this sense, we will refer to the expiration as a legal institution of public order that has as a consequence the loss of competence of the authority due to time, the same one that operates in its own right. The expiration can be manifested during the procedure or in the exercise of a power; thus, we will refer to articles 26, 48, 56 and 71 of the LOCGE, with the support of the analysis units (sentences) and the jurisprudential precedents that the National Court of Justice has dictated.